Inside Cover: Effect of C7 Modifications on Benzothiadiazine‐1, 1‐dioxide Derivatives on Their Inhibitory Activity and Selectivity toward Aldose Reductase (ChemMedChem 4/2013). Issue 4 (25th March 2013) - Zhang, Shuzhen; Chen, Xin; Parveen, Shagufta; Hussain, Saghir; Yang, Yanchun; Jing, Chaojun; Zhu, Changjin
<x xml:space="preserve">Abstract</x> The inside cover picture shows a benzothiadiazine‐1, 1‐dioxide inhibitor of aldose reductase (ALR2) bound in the active site. Structure–activity relationship studies led to inhibitors with enhanced activity and selectivity, highlighting the important role of the C7 side chain and providing insight into the pharmacophore requirements for ALR2 inhibition. For more details, see the Full Paper by Changjin Zhu et al. on p. 603 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>